CAPITAL INTENSITY, OPENNESS, AND THE ECONOMIC GROWTH OF THE ASEAN 5 - Ni Putu Wiwin Setyari; Surya Dewi Rustariyuni; Luh Putu Aswitari (Journal of Indonesian Economy and Business (JIEB), 2016)
One of the core elements of the neoclassical growth theory is that poor countries have low capital-labor ratios but have higher marginal products of capital than the rich countries. This means the low-income countries experience faster growth rates and become a reason for allowing capital, goods, and technology can move across countries. Assuming that the labor intensive countries have higher returns on capital, then investment will flows into those countries and encourage higher economic growth. However, in fact capital flows seems to go in the opposite direction. A country with abundant capital can expand its capital-intensive sectors and export their goods along with trade liberalization. Consequently, the returns to capital in its capital-intensive sectors rise and a greater demand for investment induces higher capital inflows from abroad. Those predictions push developing countries to change their labor intensive industrial structures and become more capital intensive, to encourage their economic growth. This paper examines how capital intensity and openness affect economic growth using data from the ASEAN 5 countries data. The issue of endogeneity and unobserved heterogeneity, as major problems in a data panel, are addressed by the fixed effect method and the Feasible General Least Square (FGLS). Capital flows appears to be the most important source of economic growth, whilst trade is found to have a limited role. The interaction between capital intensity and the openness indicator do not indicate significant effects. Generally, there is no evidence that the more outward-oriented countries with high levels of capital intensity experiences higher economic growth.